Turnover of Information Technology Professionals: A Narrative Review, Meta-Analytic Structural Equation Modeling, and Model Development1 - Joseph, Damien; Ng, Kok-Yee; Koh, Christine; Ang, Soon (MIS Quarterly, 2007)
This study combines a narrative review with meta-analytic techniques to yield important insights about the existing research on turnover of information technology professionals. Our narrative review of 33 studies shows that the 43 antecedents to turnover intentions of IT professionals could be mapped onto March and Simon’s (1958) distal-proximal turnover framework. Our meta-analytic structural equation modeling shows that proximal constructs of job satisfaction (reflecting the lack of desire to move) and perceived job alternatives (reflecting ease of movement) partially mediate the relationships between the more distal individual attributes, job-related and perceived organizational factors, and IT turnover intentions. Building on the findings from our review, we propose a new theoretical model of IT turnover that presents propositions for future research to address existing gaps in the IT literature.